Hubungan Asupan Energi Dan Asupan Protein Dengan Status Gizi Narapidana Di Lembaga Pemasyarakatan Klas 1 Cirebon - Andari, Mega Meirisa Fitri, Luluk Ria Rakhma, S.Gz., M.Gizi (2017)
Food consumption provided in detention and prisons for inmates is lower than the nutritional requirement recommended by Indonesian Health Ministry. Previous study conducted by the Ministry of Health and Ministry of Justice show that the prevalence of malnutrition and diseases associated with nutrition were 14,3% and 40,9% respectively. Objective this study to determine association of energy intake and protein intake to nutritional status of prisoner at Lembaga Pemasyarakatan Klas 1 Cirebon. This is an observational study with cross sectional approach, 50 respondents of 580 population were recruited using systematic random sampling. Data on energy and protein intake were obtained using Comstock and 3-day food recall method. The assesement of nutritional status obtained using anthropometric measurements of weight ang height. Data were analyzed using Pearson Product Moment. The result showed that 66,7% of respondents had energy intake of 90-110% of requirement and normal nutritional status, while 75% of respondents had protein intake of 70-79% of requirement and normal nutritional status. Pearson Product Moment results showed no association between energy intake and nutritional status p=0,367 and no association was found between protein intake and nutritional status p=0,053. Keywords: Prison , Energy Intake, Protein Intake, Nutritional Status